Identification of a novel E‐box binding pyrrole‐imidazole polyamide inhibiting MYC‐driven cell proliferation. Issue 4 (3rd March 2015) - Mishra, Rajeev; Watanabe, Takayoshi; Kimura, Makoto T.; Koshikawa, Nobuko; Ikeda, Maki; Uekusa, Shota; Kawashima, Hiroyuki; Wang, Xiaofei; Igarashi, Jun; Choudhury, Diptiman; Grandori, Carla; Kemp, Christopher J.; et al.
Abstract : The MYC transcription factor plays a crucial role in the regulation of cell cycle progression, apoptosis, angiogenesis, and cellular transformation. Due to its oncogenic activities and overexpression in a majority of human cancers, it is an interesting target for novel drug therapies. MYC binding to the E‐box (5′‐CACGTGT‐3′) sequence at gene promoters contributes to more than 4000 MYC‐dependent transcripts. Owing to its importance in MYC regulation, we designed a novel sequence‐specific DNA‐binding pyrrole–imidazole (PI) polyamide, Myc‐5, that recognizes the E‐box consensus sequence. Bioinformatics analysis revealed that the Myc‐5 binding sequence appeared in 5′‐ MYC binding E‐box sequences at the eIF4G1, CCND1, and CDK4 gene promoters. Furthermore, ChIP coupled with detection by quantitative PCR indicated that Myc‐5 has the ability to inhibit MYC binding at the target gene promoters and thus cause downregulation at the mRNA level and protein expression of its target genes in human Burkitt's lymphoma model cell line, P493.6, carrying an inducible MYC repression system and the K562 (human chronic myelogenous leukemia) cell line. Single i.v. injection of Myc‐5 at 7.5 mg/kg dose caused significant tumor growth inhibition in a MYC‐dependent tumor xenograft model without evidence of toxicity. We report here a compelling rationale for the identification of a PI polyamide that inhibits a part of E‐box‐mediated MYC downstream gene expression and is a model for showing that phenotype‐associated MYC downstream gene targets consequently inhibit MYC‐dependent tumor growth. Abstract : The present work emphasizes a novel approach in cancer therapeutics using sequence specific DNA binding Pyrrole‐Imidazole (PI) polyamide, Myc‐5, which recognize 8 bp of the sequence including E‐box consensus of CACGTG sequence. The Myc‐5 bound to E‐box of a subset of MYC downstream genes in a target specific manner, thereby down‐regulating gene and protein expression of those downstream genes and subsequently suppressed MYC‐dependent tumorigenesis of xenograft model of B‐cell lymphomas in SCID mice by inhibiting proliferation and inducing apoptosis. Conclusively our findings suggest that E‐box binding PI polyamide can be used in MYC downstream‐targeting therapies for cancer treatment.